Are urban mangroves emerging hotspots of non-indigenous species? A study on the dynamics of macrobenthic fouling communities in fringing red mangrove prop roots (2023)
ABSTRACT: Urbanization represents a radical transformation of natural habitats that alters all the biotic and abiotic properties governing ecosystems. Urban expansion often results in oversimplified communities, where most specialists decline or disappear and a few generalist or exotic species become dominant. The consequences of urban expansion in mangrove forests are understudied, although these systems have been altered by humans for centuries and the growth of human population in tropical coasts is expected to be faster than in higher latitudes. To assess the importance of indigenous and non-indigenous species in driving temporal and spatial changes in community structure of red-mangrove prop-root macrobenthic communities, we studied heavily altered mangrove forests from two bays from the Caribbean coast of Colombia in 2005 and 2021. In all places/periods, the community richness was low, a few taxa were dominant (11 taxa, out of 40, comprised~90% of the total abundance) and 35% of those taxa were non-indigenous species whose presence is related with known stressors in urbanized systems. Hence, call for efforts to assess whether urban mangrove forests are emerging as hotspots for non-indigenous biota. Community structure did not change within or between bays, there was a clear, significant turnover of core species between 2005 and 2021, with non-indigenous species playing a prominent role in this variability. This was puzzling—ecological theory asserts that the abundance of a species is related to their permanence: core species are relatively stable through time, while rare species appear or disappear—but this may not apply for stressed communities influenced by non-indigenous biota.